“Din eğitimi açısından Kur’an’da Hz. İbrahim (a.s.)” - Gürel, Ramazan (My University, 2011)
Hz. İbrahim’in Kur’an-ı Kerim’deki kişiliği çok zengin ve kompleks yapıda olup İslam geleneği içerisinde farklı yönlere odaklanmış değişik boyutları barındırır. Kur’an-ı Kerim’de yirmi beş surede yer alan iki yüz kırk beş ayet, Hz. İbrahim ile ilgilidir. Surelerden biri de Hz. İbrahim’in adını taşır. Bu ayetleri incelersek hem onun örnek modelliğinin köklerinin izlerini hem de inanç ve yaşam tarzının kolayca fark edebiliriz. Hz. İbrahim, Hz. Nuh’un soyundandır ve selim bir kalbe sahiptir. Onun getirdiği mesaj, Hz. Nuh’tan sonra fakat Hz. Musa, Hz. İsa ve Hz. Muhammet’ten öncedir. O, “Allah’ın dostu” / halilullah olarak isimlendirilir. Babasını ve kavmini tevhide davet etmiştir. Kur’an-ı Kerim, onun bir Yahudi veya Hıristiyan olmadığını, kendini Allah’a adamış, Hanif bir Müslüman olduğunu bildirir. Özellikle tevhide olan saf imanı, onun bu şekilde anılmasını sağlamıştır. Kur’an-ı Kerim’deki bağlamına göre Hz. İbrahim’in kavmi putlara taparken o, âlemlerin Rabbini putlardan ayrı tutmuştur. İnandığı ilahı, “yaratan, besleyen, yargılayan, affeden, yaşatan, öldürüp dirilten ve ahiret gününün sahibi olan Allah” olarak tanıtmıştır. Fakat Hz. İbrahim’in kavminin ona cevabı, “bunu öldürün veya yakın!” demek olmuştur.

The personality of Ibrahim in the Quran is very rich and complex and its different dimentions have been focused on by different tendencies within the Islamic tradition. In the Qur’an, two hundred and forty-five verses contained in twenty-five suras are dedicated to Ibrahim, no complete single account can be found but one of the suras (14.) bears his name. Throughout these verses, we can eseaily trace the roots of a prototype figure both in his faith and way of life. Ibrahim belongs to the path (shia, lineage) of Noah (that is Nova) and has a free heart (qalb selim), He is among those to whom the religion was prescribed after Noah, but before Musa (that is Moses), Isa (that is Jesus) and Muhammed. He is called “intimate friend of God” (halilullah). He preaches monotheism to his father and his people. The Qur’an declares that Ibrahim was not a Jew, nor a Christian; but he was an upright man (hanif), a muslim who had surrendered himself to God. He is said in this particular occasion to be ‘hanif’, a monotheistic believer, or a pure (true) muslim. According to the Qur’anic text “their idols are given a rough time and Ibrahim exalts the blessings of the Lord of the worlds who directs him, feeds him and forgives him, just as he makes him live, die and rise again, for he is the master of the eschatological times”. But the response of his fellow was to “kill him or burn him”.
Keywords: Din Eğitimi; Kur’an-ı Kerim; Peygamberler_Din Eğtimi